Modulation of Hydrophobic Interaction by Mediating Surface Nanoscale Structure and Chemistry, not Monotonically by Hydrophobicity. Issue 37 (13th August 2018) - Cui, Xin; Liu, Jing; Xie, Lei; Huang, Jun; Liu, Qi; Israelachvili, Jacob N.; Zeng, Hongbo
Abstract: The hydrophobic (HB) interaction plays a critical role in many colloidal and interfacial phenomena, biophysical and industrial processes. Surface hydrophobicity, characterized by the water contact angle, is generally considered the most dominant parameter determining the HB interaction. Herein, we quantified the HB interactions between air bubbles and a series of hydrophobic surfaces with different nanoscale structures and surface chemistry in aqueous media using a bubble probe atomic force microscopy (AFM). Surprisingly, it is discovered that surfaces of similar hydrophobicity can show different ranges of HB interactions, while surfaces of different hydrophobicity can have similar ranges of HB interaction. The increased heterogeneity of the surface nanoscale structure and chemistry can effectively decrease the decay length of HB interaction from 1.60 nm to 0.35 nm. Our work provides insights into the physical mechanism of HB interaction. Abstract : Bubble wrapped : Using bubble‐probe AFM coupled with theoretical analysis, the hydrophobic interactions of air bubbles with alkanethiol self‐assembled monolayers and oil‐infused porous surfaces were determined. The range of the hydrophobic interaction strongly depends on the degree of the water structuring effect, which could be effectively modulated by mediating the surface nanoscale structure and surface chemistry.